Infrastructure and economic geography: An overview of theory and evidence - Gianmarco I. P. Ottaviano (EIB Papers, 2008)
This essay provides an overview of the role of infrastructure on economic geography in the light of both theoretical and empirical findings. Two main lessons stand out. First, infrastructural improvements affect the geographical distribution of economic activities. Second, even when localized, infrastructure investment generates externalities that may diffuse quite far across the economy. These two lessons have two far-reaching policy implications. First, effective infrastructure projects require knowledge on their impacts on the spatial distribution of economic activities. These impacts depend crucially on the specific details of the projects and the specific sources of agglomeration economies they affect. Second, regions need to coordinate not only in terms of interregional infrastructure projects but also in terms of intraregional ones if they want to avoid beggar-thyneighbour and self-defeating outcomes.
Keywords: 330; Infrastruktur; Räumliche Verteilung; Regionale Wirtschaftsstruktur